2018
DOI: 10.1161/circresaha.118.312804
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Nonfoamy Rather Than Foamy Plaque Macrophages Are Proinflammatory in Atherosclerotic Murine Models

Abstract: Rationale: Monocyte infiltration into the subintimal space and their intracellular lipid accumulation are the most prominent features of atherosclerosis. To understand the pathophysiology of atherosclerotic disease, we need to understand the characteristics of lipid-laden foamy macrophages in the subintimal space during atherosclerosis. Objective: We sought to examine the transcriptomic profiles of foamy and non-foamy macrophages isolated from atherosclerotic intima. Methods and Results: Single-cell RNA-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
416
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(448 citation statements)
references
References 52 publications
(59 reference statements)
30
416
1
1
Order By: Relevance
“…In addition, the investigation of orthologous gene signatures derived from murine lipid-associated macrophages (LAM), which were shown to be monocyte-derived by lineage tracing and also detected in human adipose tissue (Jaitin et al, 2019), again revealed the strongest enrichment in mono-like and C1Q + AMs ( Figure 7B). The same was also true for orthologous genes derived from Trem2 + foam cells of atherosclerotic plaques in mice (Kim et al, 2018) (Figure 7B), which were found by Lin et al to originate from monocytes (Lin et al, 2019), supporting the hypothesis that mono-like and C1Q + AMs are actually derived from monocytes.…”
Section: Amssupporting
confidence: 81%
“…In addition, the investigation of orthologous gene signatures derived from murine lipid-associated macrophages (LAM), which were shown to be monocyte-derived by lineage tracing and also detected in human adipose tissue (Jaitin et al, 2019), again revealed the strongest enrichment in mono-like and C1Q + AMs ( Figure 7B). The same was also true for orthologous genes derived from Trem2 + foam cells of atherosclerotic plaques in mice (Kim et al, 2018) (Figure 7B), which were found by Lin et al to originate from monocytes (Lin et al, 2019), supporting the hypothesis that mono-like and C1Q + AMs are actually derived from monocytes.…”
Section: Amssupporting
confidence: 81%
“…3b), though the genes involved are completely distinct between species 1 . Second, an emerging theme in recent mouse DAM literature is the role of lipid and lysosomal biology: many mouse DAM genes such as apoe , Ch25h , Lpl , Ctsb and Atp6v0d2 are known to function in lipid and lysosomal biology and can be induced by lipid pathologies including demyelination 16 and atherosclerosis 17,18 . In our data, in addition to APOE , we found that the lipoprotein receptor LSR and the lysosomal enzyme ARSA —homozygous mutations in which cause metachromatic leukodystrophy 19 —are elevated in myeloid cells from AD patients.…”
Section: Main Textmentioning
confidence: 99%
“…The recent development of single-cell RNA-sequencing (scRNA-seq) in highthroughput allows investigating immune cell transcriptional states in disease models with high resolution, and has recently been employed to uncover novel immune cell transcriptional states in e.g. myocardial infarction (13), (14) or atherosclerosis (15), (16). Furthermore, novel methods of oligonucleotide-barcoded antibody labeling of cells prior to their processing for scRNA-seq allows a multimodal measurement of the expression of cell surface epitopes in addition to transcripts expression (17), (18) and the multiplexing of several biological samples in a single scRNA-seq library (19).…”
Section: Introductionmentioning
confidence: 99%